Application of atomic force microscopy for characterizing membrane biofouling in the micrometer and nanometer scales. Issue 3 (27th March 2012) - Zaky, Amr M.; Escobar, Isabel C.; Gruden, Cyndee L.
<x xml:space="preserve">Abstract</x> Despite the availability of new detection and monitoring methods, a complete understanding of biofouling is still lacking. Therefore, this study employed a combination of biofilm characterization protocols macro, micro, and nano (meter) scales to provide insight into the early stages of biofilm formation using cellulose acetate ultrafiltration membranes. Membranes were fouled during 53 hours of crossflow filtration using two distinct feed waters. Biofilm characterization techniques included flux decline, image analysis, and atomic force microscopy (AFM). The flux decline and image analysis (bulk biofilm surface area coverage) data could not be correlated with feed water characteristics. Using AFM, it was possible to provide feature height analyses on the nano‐ scale to verify distinct biofilm distribution and formation as function of feed water characteristics. These findings suggest that AFM‐based biofilm characterization may provide the details needed to distinguish variations in cell deposition on a single membrane surface and/or between varied feed waters. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 449–457, 2013